Supply Chain Resilience: Definitions and quantitative modelling approaches – A literature review. (January 2018) - Pires Ribeiro, João; Barbosa-Povoa, Ana
Highlights: A literature review on Supply Chain Resilience Quantitative Models is performed. Is presented a study on SC Resilience definitions and a framework is proposed. The relationship between SC Resilience and Risk is analysed. Research gaps and future directions on SC Resilience Quantitative Models are identified. Abstract: Resilience is currently an increasing concern in supply chain (SC), caused by their globalization, which is subject to diverse types of disturbances. Such disturbances need to be handled in the right way, compelling the use of tools that can support resilient supply chain decisions. To comprehend how the academic community has been treating such concern we developed a systematic literature review on SC resilience, focusing on the analysis of the development of quantitative methods to support such decisions. A content analysis was performed, in an identified sample of 39 papers, exploiting a solid methodology in the preparation; collection; and analysis of the information obtained. Additionally, published SC resilience definitions were examined and, as result, it was found that there is no consensus in the literature. A sound definition is then proposed, which is supported by a comprehensive framework that includes the four main identified SCR elements: focus event; adaptive framing or adaptive response; speed; performance level. Moreover, it was concluded that the use of quantitative models, although recognised with high relevance in SC resilience, should be further researched as most of the published work explores the conceptualization of only a limited number of resilience elements, lacking the development of integrated holistic approaches. These should simultaneously address the main supply chain characteristics and SC resilience elements. Future directions for the academic community are presented, aiming to guide future research work in the area.